(untitled) (CIPEEX, 2025)
This abstract aimed to outline the differences between Pathogen-Associated Molecular Patterns (PAMP) and Damage-Associated Molecular Patterns (DAMP). The innate immune response is the body’s first line of defense against infections and tissue damage, and is characterized by a rapid, non-specific and memoryless response, which is mediated by molecules, cells, tissues and organs capable of recognizing patterns conserved in pathogens or signs of endogenous danger. PAMPs are conserved molecules present in pathogens that will be recognized by Pattern Recognition Receptors (PRR), expressed by cells of the innate immune system, such as neutrophils, monocytes, macrophages and dendritic cells. An example of RRP is Toll-like receptors (TLR), present in the plasma membrane and endosomes. RRPs will recognize PAMP/DAMP, in a lock-and-key mechanism, which will be the beginning of the innate immune response. Examples of PAMP include bacterial lipopolysaccharides (LPS), peptidoglycans, flagellin, viral nucleic acids, etc. This interaction indicates the presence of microbial invasion. Which is different from the PRR-DAMP interaction. DAMP refers to molecules released by damaged or stressed cells. Thus, they act as danger signals that alert the immune system to tissue damage by promoting modulation of the inflammatory response. Examples of DAMP include mitochondrial proteins, extracellular ATP, heat shock proteins, and uric acid, among others. Although both molecular patterns are detected by PRR, such as Toll-like receptors (TLR) and NOD-like receptors (NLR), present in the cytoplasm, the main difference lies in the origin of the signals. While PAMP alerts the immune system to the presence of infectious agents, often exogenous, DAMP signals internal tissue damage, regardless of infection with therapeutic implications. Understanding these differences is essential for the advancement of therapeutic strategies aimed at controlling inflammation and autoimmune diseases, as well as for the development of vaccines and immunomodulatory treatments.